Facile Synthesis of N-Doped Graphene-Like Carbon Nanoflakes as Efficient and Stable Electrocatalysts for the Oxygen Reduction Reaction - Gu, Daguo; Zhou, Yao; Ma, Ruguang; Wang, Fangfang; Liu, Qian; Wang, Jiacheng (Nano-Micro Letters, 2017)
A series of N-doped carbon materials (NCs) were synthesized by using biomass citric acid and dicyandiamide as renewable raw materials via a facile one-step pyrolysis method. The characterization of microstructural features shows that the NCs samples are composed of few-layered graphene-like nanoflakes with controlled in situ N doping, which is attributed to the confined pyrolysis of citric acid within the interlayers of the dicyandiamide-derived g-C3N4 with high nitrogen contents. Evidently, the pore volumes of the NCs increased with the increasing content of dicyandiamide in the precursor. Among these samples, the NCs nanoflakes prepared with the citric acid/dicyandiamide mass ratio of 1:6, NC-6, show the highest N content of 6.2 at%, in which pyridinic and graphitic N groups are predominant. Compared to the commercial Pt/C catalyst, the as-prepared NC-6 exhibits a small negative shift of 66 mV at the half-wave potential, demonstrating excellent electrocatalytic activity in the oxygen reduction reaction. Moreover, NC-6 also shows better long-term stability and resistance to methanol crossover compared to Pt/C. The efficient and stable performance are attributed to the graphene-like microstructure and high content of pyridinic and graphitic doped nitrogen in the sample, which creates more active sites as well as facilitating charge transfer due to the close four-electron reaction pathway. The superior electrocatalytic activity coupled with the facile synthetic method presents a new pathway to cost-effective electrocatalysts for practical fuel cells or metal–air batteries. Highlights: 1 N-doped carbon nanoflakes (NCs) were synthesized via facile one-pot pyrolysis of citric acid and dicyanamide. 2 The as-synthesized NCs have a stacked, few-layered graphene-like structure enriched with pyridinic and graphitic N groups. 3 The optimized NCs show better long-term stability and highly active in electrocatalytic oxygen reduction with a close four-electron reaction pathway.